THE ROLE OF PLASMIDS IN RESISTANCE OF Kl. pneumoniae ANTIBIOTICS - KHALAF JASIM MOHAMMED AL-DOLAIMI (مجلة جامعة الانبار للعلوم الصرفة, 2012)
The bacterium Kl. pneumoniae was isolated from urine sample of patient with urinary tract infection and diagnosed according to its cultural and microscopic characters and biochemical reactions . Sensitivity test of the bacterium against antibiotics was established and the results appeared that the bacterium was Sensitive to Amoxycillin , Gentamycin , Cephaloxin, Neomycin, Rifampicin , Chloramphenicol , Tobramycin , Ampicillin and carpenicillin and resistant to clindomycin ,cloxacillin , Trimethprim , Cefalotine , Vancomycin , Penicillin G , Lincomycin , Fusidic acid , Metronidazole and Nalidixic acid . Results of plasmid DNA content for the bacterium showed the presence of 8-6 kb plasmid compared with the plasmid pBR 322 isolated from E. coli HBlol . To study the role of plasmids in coding for antibiotics resistance , curing experiment was accomplished using SDS .Results showed the loss of resistance of the antibiotic , Nalidixic acid after physical loss of plasmid as ensured by gel electrophoresis.